A magyar agrárexport kereskedelmi előnyei és versenyképessége az EU piacán - Imre Fertő (Hungarian Academy of Sciences, Institute of Economics, 2008)
– The complementarities of trade advantage and trade competitiveness measures for Hungarian agro-food trade with the European Union are analyzed. The stability and duration of the trade measures over time is investigated by the survival analysis using the nonparametric Kaplan-Meier product limit estimator and the consistency test between the trade measures is conducted by the stratified Cox proportional hazard model. Hungary experienced greater number of products with relative trade disadvantages and greater significance of one-way imports. Hungary experienced relative trade advantages for bulk raw commodities, processed intermediates, and horticulture, with the greatest significance of successful quality competition and one-way exports, and the lowest significance of unsuccessful price and unsuccessful quality competition. The duration of relative trade advantages is longer than the duration for the successful trade competition categories. Our results confirm that the relative trade advantage is consistent with the one-way export and the successful price and successful quality competition categories in two-way trade on one side, and the relative trade disadvantage with the one-way import and the unsuccessful price and unsuccessful quality competition on the other.
Keywords: Q12; 330; trade advantage; price and quality competitiveness; agri-food trade; Außenhandel; Lebensmittel; Internationaler Wettbewerb; Wettbewerbsvorteil; Statistische Bestandsanalyse; Schätzung; Ungarn; EU-Staaten